The new cosmopolitan world atlas (Chicago, 1968)
In the "Reference maps of continents, oceans, and countries": Delicate shading portrays the earth's terrain and serves as a framework upon which detail of names, intricate communications networks, rivers, lakes, and seas are symbolized. Colored boundaries emphasize the important political format gives each two-page map a full 22"* 14 3/4" spread and scale large enough to accurately present important spatial information. In the "Individual U.S. and Canadian Province maps": Essential detail for in-depth study of areas close to home and for detailed planning is shown on these maps. Each map, page captures the unique aspects of terrain, road and railroad patterns, county boundaries, and cities that characterize individual states and provinces. More than 69.000 indexed places is an indispensable part of the atlas. The book also has extensive tables that classify such material for easy access and comparison. Tables list the size, population, capitals, and political status of countries; the earth's movements and sizes of continents; the highest, lowest, deepest, and longest; the populations of over 12.000 important places in the world; and the 1990 census populations and zip-codes for cities in the United States. A world time-zone maps is included. "This Fragile Earth" is a contemporary graphic exposition on the state of the world's resources and the use and misuse of those resources. World maps of population, climate, vegetation, environments and specific concerns, ponctuate this richly illustrated 32-page section. It adds information that increases the scope and usefulness of this already fact-filled atlas. On "Using the Atlas", important concepts about map scale, direction, the reference system, symbolization, and atlas organization help make the best use of the wide range of information contained between the atlas covers
Keywords: Atlases,Bản đồ